Procrastination, Perfectionism, and Other Work-Related Mental Problems: Prevalence, Types, Assessment, and Treatment—A Scoping Review - Steinert, Christiane; Heim, Nikolas; Leichsenring, Falk (Frontiers in Psychiatry, 2021)
Work-related mental problems can be defined as behaviors and cognitions that impede the successful completion of a task in a given time frame, i.e., the difficulty or inability to achieve important work-related goals. They are highly prevalent but have been neglected in psychology in general and as a target of psychotherapy in particular. Although work-related problems do not represent a mental disorder per se, they are associated with severe distress and high psychosocial costs. In this article, the prevalence of work-related problems, associated burden, diagnostic assessment and treatment are reviewed. So far, research has primarily focused on procrastination, i.e., the act of postponing or delaying tasks until the last minute or past the deadline. However, procrastination represents just one type of work-related problems among several others. Further forms of work-related problems are presented (e.g., perfectionism, or work-related problems in the context of specific personality types). The relation of work-related problems to specific mental disorders is discussed. Psychotherapy is the treatment of choice for work-related mental problems. However, response rates for the treatment of procrastination are limited, which calls for further research into which treatments work for whom. No evidence-based treatments are currently available for other types of work-related problems, with the exception of perfectionism, a personality trait that is also linked to problems in the field of work. Thus, there is a need to further improve the treatment of work-related problems including procrastination. For other types of work-related problems, effective treatments need to be developed and validated. They may be based on existing manualized treatments and extended by specific aspects or modules focusing on work-related problems.